Conserving the Gems of Upper Baleh Kapit, Sarawak - Tonga, Noweg; Jongkar, Grinang; Peter, Cindy; Lip, Belinda Hun Mei; Aisah, Eden; Michael, Ngelai; Jiwari, Abdullah; Mohamad Irwan, Aman (UNIMAS Publisher, 2019)
The State Government of Sarawak has declared 2.7 million hectares as an area for conservation and sustainable development under the Heart of Borneo (HoB) Initiative. The forest of Upper Baleh River in Kapit Division has been proposed as national park within the HoB which encompasses an area of 66,721 ha, bordering West Kalimantan, Indonesia. The national park is important for wildlife connectivity to protect species of flora and fauna and their natural habitats within the region. The area, being the headwater area for Baleh River, is also significant for the development of hydroelectric power by Sarawak Energy Berhad, providing water security to generate hydroelectric power. In line with the significant functions of Upper Baleh, four agencies, the Forest Department Sarawak, World Wide Fund for Nature Malaysia (WWF-Malaysia), Sarawak Energy Berhad and Universiti Malaysia Sarawak conducted a two-week expedition to the area in November 2015 to gather baseline information to support the gazettement of the park and a catchment management plan. Conserving the Gems of Upper Baleh is an appropriate title for this book, as it aims to share some of the outstanding findings of the expedition that highlights the unique biodiversity and importance of the area for conservation. We would also like to acknowledge Ms. Cynthia Chin and Jason Hon of WWF-Malaysia, and Indraneil Das for their constructive comments on the draft, and UNIMAS Publisher, the designer Mr. Mohamad Nazri Mario, Mr. Abang Zainuddin Abang Haji Sharkawi and Dr Jane Labadin for their inputs in making this book an enjoyable one.